If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(r + 4) = -8r + -18 Reorder the terms: -6(4 + r) = -8r + -18 (4 * -6 + r * -6) = -8r + -18 (-24 + -6r) = -8r + -18 Reorder the terms: -24 + -6r = -18 + -8r Solving -24 + -6r = -18 + -8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '8r' to each side of the equation. -24 + -6r + 8r = -18 + -8r + 8r Combine like terms: -6r + 8r = 2r -24 + 2r = -18 + -8r + 8r Combine like terms: -8r + 8r = 0 -24 + 2r = -18 + 0 -24 + 2r = -18 Add '24' to each side of the equation. -24 + 24 + 2r = -18 + 24 Combine like terms: -24 + 24 = 0 0 + 2r = -18 + 24 2r = -18 + 24 Combine like terms: -18 + 24 = 6 2r = 6 Divide each side by '2'. r = 3 Simplifying r = 3
| 2r^2-8r-10=0 | | -4(9s-7)=35+5s | | Y-6=8+3 | | 5+3x=x+5+2x | | 7(R-11)-6r= | | Y=(8x+3)(x-8) | | -2p+7=14+1+4p+4 | | 5.75x+5=9.25x+1 | | 20-x-1=4 | | 48-x^2+2x=0 | | 5y+yz= | | 21x^2+10=-5 | | 4+6m=1+7m+2 | | 11+2b=3(-2b) | | 36=35+n | | 13x^2+16x+11=0 | | -8x-9=76-40 | | -2(1+4n)-2=-6(n-3) | | 5-2p+7p=-13+2p | | -3k+7k=4k-4 | | A=4r*2(r*2) | | 3x^2-18x=-3x^2-5x-7 | | a^2-2n-8=o | | 6=-8u+2 | | Y=1.5x+15 | | 29=5+b | | 5y-12=6y-1 | | =5+b | | -9x=-3y-24 | | 17+14b=409 | | 720=8y-80+2y | | 2x-4x^2+3=0 |